Visual Politics of Japanese Majolica Tiles in Colonial South Asia - AKI TOYOYAMA (The Journal of Indian and Asian Studies)
This paper examines the political, socio-economic, and cultural aspects of Japanese decorative tiles or the so-called majolica tiles widely diffused in colonial South Asia in the early twentieth century. A tile became a popular building material in European countries by the first half of the nineteenth century, and European tiles spread over the world with the expansion of colonialism. Japan in the making of a modern nation established domestic manufacturing of tiles mainly after British models, and the industry’s rapid development was helped by the First World War (1914–1918) and the Great Kanto Earthquake (1923). The Japanese tile industry successfully entered into foreign markets, among which India was the largest and most important market that resulted in developing a variety of new Indian or Hindu designs associated with the rise of nationalism and mode of consumption. Not only within India, tiles, however, also played a crucial role in formulating cosmopolitan identities of migrant mercantile networks exemplified by the Chettiar architecture in South and Southeast Asia. However, in the late 1930s, cosmopolitanism shared by different communities in colonial urban settings became overwhelmed by nationalisms as seen in Sri Lanka where Japanese majolica tiles were differently used as a means to express religiously-regulated nationalisms in the Chettiar and Sinhalese Buddhist architecture. Thus, the analysis reveals visual politics of different religious nationalisms symbolized by Japanese majolica tiles in the interwar period that still structure the present visualscapes.